2014
DOI: 10.1188/14.cjon.321-326
|View full text |Cite
|
Sign up to set email alerts
|

Standardizing Central Venous Catheter Care by Using Observations From Patients With Cancer

Abstract: To understand the vulnerability of patients with cancer to central line-associated bloodstream infections related to tunneled central venous catheters (CVCs), patients were asked to describe their line care at home and in clinic and to characterize their knowledge and experience managing CVCs. Forty-five adult patients with cancer were recruited to participate. Patients were interviewed about the type of line, duration of use, and observations of variations in line care. They also were asked about differences … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…4,7,8,15,16 Similar to the findings of the current study, a survey of adult patient central line care also demonstrated practice variation and patient uncertainty over appropriate central line maintenance care techniques. 11 As 34% of respondents in the current survey reported that they touch or access their child’s central line, and 8% reported that another adult in the household touches or accesses their child’s central line, this study suggests the need for effective educational interventions and auditing of home caregiver central line practices. Our institutional experience suggests auditing and observations of family line care is feasible, can be positively received by families, and can be associated with reduced CLABSIs, 4 although it clearly needs to be augmented to achieve consistent central line care.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…4,7,8,15,16 Similar to the findings of the current study, a survey of adult patient central line care also demonstrated practice variation and patient uncertainty over appropriate central line maintenance care techniques. 11 As 34% of respondents in the current survey reported that they touch or access their child’s central line, and 8% reported that another adult in the household touches or accesses their child’s central line, this study suggests the need for effective educational interventions and auditing of home caregiver central line practices. Our institutional experience suggests auditing and observations of family line care is feasible, can be positively received by families, and can be associated with reduced CLABSIs, 4 although it clearly needs to be augmented to achieve consistent central line care.…”
Section: Discussionmentioning
confidence: 69%
“…10 A different group of adult oncology patients identified appreciable differences in clinic nurse central line care practices, and these patients reported variations in central line maintenance practices in their home setting. 11 It is unclear if results for adults can be translated to the unique setting presented by pediatric oncology patients, where an adult caregiver and the patient together often provide central line care, and multiple stressors contribute to quality of life. 12 …”
mentioning
confidence: 99%
“…In a 2014 survey of 47 patients at a specialized cancer center, seven of 20 respondents reported never receiving education on home management of their device, and 29% of 44 respondents did not know which symptoms would be concerning for an infection in the device. Interestingly, patients were closely observant of the protocols followed by health care personnel and were able to actively correct mistakes, such as missed flushes, short cleaning times, etc …”
Section: Patient Educationmentioning
confidence: 99%
“…Interestingly, patients were closely observant of the protocols followed by health care personnel and were able to actively correct mistakes, such as missed flushes, short cleaning times, etc. 45…”
Section: Patient Educationmentioning
confidence: 99%
“…Patients with TIAP, compared to patients with CVC, reported less restriction in daily activities and spent less time thinking that they had a CVAD [23]. However, regarding CVAD, cancer patients feel very cautious and insecure [24]. Maybe, they recognize that CVADs like TIAP require utmost care to minimize not only infection risk [25] but also other complications like catheter malfunction or catheter-related thromboembolism [26][27][28].…”
Section: Introductionmentioning
confidence: 96%